À la recherche du temps perdu: la Cour suprême et l'interprétation des droits linguistiques constitutionnels dans les années 80 - Riddell, Alan (Les Cahiers de droit, 1988)
During the seventies and early eighties, the Supreme Court adopted a broad, purposive and organic approach to the interpretation of language rights in the Constitution. In 1986, however, the Court implicitely repudiated this approach and returned to a narrow, literal and static interpretation of these rights, reminiscent ofthat espoused by the Privy Council during the late 19th and early 20th centuries. The author attacks the policy considerations which underlie this recent change in the Court's approach. He argues that besides impeding further enhancement of bilingualism, the change poses a threat to all minority rights and indeed to the stability of the Canadian Charter of Rights and Freedoms. In his view, the terms of the Meech Lake Accord are too ambiguous to have much effect on the Supreme Court's future interpretation of the Constitution and should therefore be altered to ensure that the Court is induced to adopt a more generous approach when interpreting French language rights.